Robert J. Thornton & Peter Skalnik (eds.): The Early Writings of Bronislaw Malinowski - Liep, John (Tidsskriftet Antropologi, 2019)
Robert J. Thornton & Peter Skalnik (eds.): The Early Writings of Bronislaw Malinowski Anmeldes af John Liep